Bis[1]benzothieno[2, 3-d:2′, 3′-d′]anthra[1, 2-b:5, 6-b′]dithiophene: synthesis, characterization, and application to organic field-effect transistors. Issue 10 (18th January 2017) - Hyodo, Keita; Hagiwara, Hideki; Toyama, Ryota; Mori, Hiroki; Soga, Shin-ichi; Nishihara, Yasushi
Abstract : A straightforward synthetic method of BBTADT having nine aromatic rings fused and evaluation of OFET in polycrystalline films are reported. Abstract : We report the straightforward synthetic method and characterization of bis[1]benzothieno[2, 3- d :2′, 3′- d ′]anthra[1, 2- b :5, 6- b ′]dithiophene (BBTADT) having nine aromatic rings fused without solubilizing groups. The highest mobility of fabricated OFETs utilizing BBTADT exhibited 2.7 × 10 −2 cm 2 V −1 s −1 in polycrystalline films formed by vapor deposition, depending on the annealing temperatures of a substrate.